A Required Carnegie Unit in the Arts - What Form Will It Take? - Campeau, Raymond ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This document describes a study to assess the change in students' responses toward the visual arts as a result of their participation in an entrance level art course. The course was structured to provide the students with an understanding of art skills, a recognition of excellence in art objects, and knowledge of diversity of delivery through style and media. The students were provided with a forum to produce, criticize, and make judgments in the visual arts. Student responses toward art works representing diverse styles and techniques were assessed at the beginning and end of the school year. Written assignments and samples of the students' art works were reproduced and kept on file along with questions that the students raised about exhibitions held in the high school gallery. This bank of information formed a data base to explicate the results of the pre and post assessments. The evidence provided by the positive assessment of the students' written responses plus the consistency of the two assessment instruments' results, one of which asked if it was all right for work to look like this, and the other a ranking of three sets of prints, reinforced and supported the original hypothesis. Students became more receptive to all art forms and their critical and productive responses moved from the naive to the quasi-professional. The students were able to accept many diverse styles of art. They became more receptive to abstract, non-objective, and other non traditional art forms. A 14-item bibliography and samples of students' work are included. (DK)
Availability: National Arts Education Research Center, New York University, 32 Washington Place, Room 52, New York, NY 10003 ($4.00).
Sponsoring Agency: National Endowment for the Arts, Washington, DC.
Sponsoring Agency: Department of Education, Washington, DC.
Teachers.
Researchers.
Practitioners.
Keywords: Art Appreciation; Art Education; Educational Research; Secondary Education; Student Attitudes; Student Reaction; Visual Arts; Reports, Research